Structural Characterization of Tungsten Oxides Supported on Titanium Silicalite - Prasetyoko, Didik; Ramli, Zainab; Endud, Salasiah; Nur, Hadi (IPTEK The Journal for Technology and Science, 2008)
Titanium silicalite (TS-1) is known as an active material catalyst in the epoxidation reaction. In this study, tungsten oxides (WO3) with various loading amount have been supported on the TS-1 to increase of the catalytic activity of the TS-1 material. The solids structure and property were investigated by X-ray diffraction (XRD), temperature programmed reduction (TPR), ultra violet-visible diffuse reflectance (UV-Vis-DR) and infrared (IR) spectroscopy and scanning electron microscopy (SEM) techniques. The results showed that the structure of TS-1 is not collapsed after impregnation of WO3. It was also found that tungsten species have interacted with the silanol groups on the surface of TS-1.